PENGARUH MUSIK KLASIK TERHADAP MEMORI JANGKA PENDEK PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS HKBP NOMMENSEN - REBECCA RUMESTY LAMTIAR; VANNESSA ANGELICA (LP2MTBM MAKARIOZ, 2022)
Learning and memory are one of the major functions of the central nervous system that are needed in everyday life. One ofthe factors that can improve short-term memory performance is by listening to music, one of which is classical music.Listening to classical music is thought to be able to form sufficient attention so that the incoming information is recordedproperly and forms a memory. This study was aimed to determine the effect of exposure to classical music on short-termmemory in medical students at the HKBP Nommensen University. The design of this research was true experiment researchin the form of pretest-posttest with control group. The sample was divided into 2 groups, each 18 students from the medicalfaculty who were completing their final project. Each group was given a short-term memory test using a memory test usingnumbers. After that, the classical music of Beethoven's Pathetique II was played for the treatment group for 30 minutes,while the control group was given a break. After 30 minutes, the test was take again and seen the score. In the group wasexposed to classical music, there were 4 students whose short-term memory scores were lower, 3 students whose shorttermmemory scores were the same and there were 11 students whose short-term memory scores were higher afterexposure to classical music. Based on the Wilcoxon test, there is a significant difference in short-term memory scoresbetween before and after exposure to classical music. Exposure to classical music has an influence on the short-termmemory of medical students at the HKBP Nommensen University.